Immediate versus delayed implant placement after anterior single tooth extraction: the timing randomized controlled clinical trial. (31st January 2017) - Tonetti, Maurizio S.; Cortellini, Pierpaolo; Graziani, Filippo; Cairo, Francesco; Lang, Niklaus P.; Abundo, Roberto; Conforti, Gian Paolo; Marquardt, Siegfried; Rasperini, Giulio; Silvestri, Maurizio; Wallkamm, Beat; Wetzel, Anton
Abstract: Aim: To compare need for bone augmentation, surgical complications, periodontal, radiographic, aesthetic and patient reported outcomes in subjects receiving implant placement at the time of extraction (Immediate Implant) or 12 weeks thereafter. Methods: Subjects requiring single tooth extraction in the anterior and premolar areas were recruited in seven private practices. Implant position and choice of platform were restoratively driven. Measurements were performed by calibrated and masked examiners. Results: IMI was unfeasible in 7.5% of cases. One hundred and 24 subjects were randomized. One implant was lost in the IMI group. IMI required bone augmentation in 72% of cases compared with 43.9% for delayed ( p = 0.01), while wound failure occurred in 26.1% and 5.3% of cases, respectively ( p = 0.02). At 1 year, IMI had deeper probing depths (4.1 ± 1.2 mm versus 3.3 ± 1.1 mm, p < 0.01). A trend for greater radiographic bone loss was observed at IMI over the initial 3‐year period ( p ‐trend < 0.01). Inadequate pink aesthetic scores were obtained in 19% of delayed and in 42% of IMI implant cases ( p = 0.03). No differences in patient reported outcomes were observed. Conclusions: Immediate implant placement should not be recommended when aesthetics are important, IMI should be limited to selected cases. Longer follow‐up is needed to assess differences in complication rates.